Establishing a Reference Baseline for Midday Stem Water Potential in Olive and Its Use for Plant-Based Irrigation Management - Shackel, Ken; Moriana, Alfonso; Marino, Giulia; Corell, Mireia; Pérez-López, David; Martin-Palomo, Maria Jose; Caruso, Tiziano; Marra, Francesco Paolo; Agüero Alcaras, Luis Martín; Milliron, Luke; Rosecrance, Richard; Fulton, Allan; et al. (Frontiers in Plant Science, 2021)
Midday stem water potential (SWP) is rapidly becoming adopted as a standard tool for plant-based irrigation management in many woody perennial crops. A reference or ‘baseline’ SWP has been used in some crops (almond, prune, grape, walnut) to account for the climatic influence of air vapor pressure deficit (VPD) on SWP under non-limiting soil moisture availability. The baseline can be determined empirically for field trees maintained under non-limiting soil moisture conditions, but such conditions are difficult to achieve for an entire season. We present the results of an alternative survey-based approach, using a large set of SWP and VPD data collected over multiple years, from irrigation experiments in olive orchards located in multiple countries (Spain, US [California], Italy, and Argentina). The relation of SWP to midday VPD across the entire data set was consistent with an upper limit SWP which declined with VPD, with the upper limit being similar to that found in Prunus. A best fit linear regression estimate for this upper limit (baseline) was found by selecting the maximum r-square and minimum probability for various upper fractions of the SWP/VPD relation. In addition to being surprisingly similar to the Prunus baseline, the olive baseline was also similar (within 0.1 MPa) to a recently published mechanistic olive SPAC model for ‘super high density’ orchard systems. Despite similarities in the baseline, the overall physiological range of SWP exhibited by olive extends to about -8 MPa, compared to about -4 MPa for economically producing almond. This may indicate a convergence of plant adaptations/acclimations to water supply at high levels of water availability, despite differences in physiological responses to low water availability (drought). Similar to its use in other crops, the olive baseline will enable more accurate and reproducible plant-based irrigation management for both full and deficit irrigation practices, and we present tentative SWP guidelines for this purpose.